If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (24) * x * x + -46x = 18 Multiply x * x 24x2 + -46x = 18 Reorder the terms: -46x + 24x2 = 18 Solving -46x + 24x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + -46x + 24x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + -46x + 24x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-9 + -23x + 12x2) = 0 Factor a trinomial. 2((-1 + -3x)(9 + -4x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + -3x)' equal to zero and attempt to solve: Simplifying -1 + -3x = 0 Solving -1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 0 + 1 -3x = 0 + 1 Combine like terms: 0 + 1 = 1 -3x = 1 Divide each side by '-3'. x = -0.3333333333 Simplifying x = -0.3333333333Subproblem 2
Set the factor '(9 + -4x)' equal to zero and attempt to solve: Simplifying 9 + -4x = 0 Solving 9 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = 0 + -9 -4x = 0 + -9 Combine like terms: 0 + -9 = -9 -4x = -9 Divide each side by '-4'. x = 2.25 Simplifying x = 2.25Solution
x = {-0.3333333333, 2.25}
| -7(n-3)=21+2n | | -6(-7+3x)-7=-31-7x | | ys+yv=t | | -5(-7b+2)=27-2b | | -a^0=0 | | 8x-4x+9=x-9+18 | | -4(r+9)=-63 | | 6x+7y=26x=43-6 | | (2x^4)(3x^2)=0 | | 16=7x+2-5x | | 3x-4-7x=2X+4+2x | | -3.8-4x=10.2 | | (x+2)(x+4)=13x+8 | | (17)x*x-11x+2=(2)x*x | | 3.8x-4x=10.2 | | 2x+6=-3x+26 | | 17-7=x | | 12-3b=5b-2 | | 2y=3x+9 | | 7(3x+9)=-(x-3) | | 9x^4=34x^2-25 | | n-4= | | 3(x-24)=9-2(x-2) | | (21)x*x-6=15x | | 14+3x-4=4x+4 | | 2x^6y^6-2x^7y^5+4x^5y^6+4x^6y^5= | | 4x^2=140 | | x-22=44 | | 3x+2=6x-23 | | 10q(16x+11)= | | 9x^3-6x^2+3= | | (6)x*x-14x=12 |